Arc assisted ultrasonic seam welding of Mg/Al joints with Zn interlayer. Issue 2 (22nd January 2016) - Dai, X.; Zhang, H.; Zhang, H.; Liu, J.; Feng, J.
Abstract : 6061 aluminium alloy and AZ31B magnesium alloy was successfully joined together with the addition of Zn interlayer by gas tungsten arc welding assisted hybrid ultrasonic seam welding. The effects of Zn interlayer on the microstructure and mechanical properties of the joints were investigated in detail. The results indicated that the Zn interlayer could restrain the formation of brittle Mg–Al IMCs, which were replaced by Mg–Zn IMCs. The maximum lap strength of the joints with Zn interlayer was ∼16.25 MPa, which was ∼30% increase over the joints without Zn interlayer. All the joint failures occurred by the interface mode rather than the pullout mode at the Mg/Zn interface.